Is urban spatial expansion on track to achieve low-carbon cities? An empirical comparative study of Xi’an and Chengdu in western China - Haifen Lei; Jennifer Koch; Hui Shi; Dan Zhao (Ecological Indicators, 2024)
Rapidly expanding urban areas constitute places of high-intensity energy consumption and, hence, major carbon emissions. There is an urgent need to systematically review the relationship between urban spatial expansion and carbon emissions at the city level, especially for cities in western China where development lags behind compared to other parts of the country, and differences among resource availability exist. Here, we conducted a systematic comparative analysis of carbon emissions and urban expansion indicators for urban spatial development. We introduce and apply an extension of the STIRPAT model to quantify the impact of urban spatial expansion on carbon emissions for the cities of Xi’an and Chengdu located in western China. The model findings indicate that both cities have reached the absolute and relative goal of carbon emissions, although they experienced a sprawling pattern. Moreover, population density for both cities displayed a negative relationship with carbon emissions, whereas road area per capita displayed a positive relationship. Since western cities have a later starting point for development, the empirical research on influencing variables of carbon emissions for western cities is important to local and regional urban spatial planning and governance. We propose further empirical studies regarding the gaps of existing urban spatial structure and low-carbon urban areas, in order to construct a systematic and scientifically sound approach to further low-carbon strategies in urban development.